Outcome of infection of C57BL/6 IL-10(−/−) mice with Campylobacter jejuni strains is correlated with genome content of open reading frames up- and down-regulated in vivo - Bell, J. A. (2012)
Human Campylobacter jejuni infection can result in an asymptomatic carrier state, watery or bloody diarrhea, bacteremia, meningitis, or autoimmune neurological sequelae. Infection outcomes of C57BL/6 IL-10(−/−) mice orally infected with twenty-two phylogenetically diverse C. jejuni sstrains were evaluated to correlate colonization and disease phenotypes with genetic composition of the strains. Variation between strains was observed in colonization, timing of development of clinical signs, and occurrence of enteric lesions. Five pathotypes of C. jejuni in C57BL/6 IL-10(−/−) mice were delineated: little or no colonization, colonization without disease, colonization with enteritis, colonization with hemorrhagic enteritis, and colonization with neurological signs with or without enteritis. Virulence gene content of ten sequenced strains was compared in silico; virulence gene content of twelve additional strains was compared using a C. jejuni pan-genome microarray. Neither total nor virulence gene content predicted pathotype; nor was pathotype correlated with multilocus sequence type. Each strain was unique with regard to absences of known virulence-related loci and/or possession of point mutations and indels, including phase variation, in virulence-related genes. An experiment in C. jejuni 11168-infected germ-free mice showed that expression levels of ninety open reading frames (ORFs) were significantly up- or down-regulated in the mouse cecum at least two-fold compared to in vitro growth. Genomic content of these ninety C. jejuni 11168 ORFs was significantly correlated with the capacity to colonize and cause enteritis in C57BL/6 IL-10(−/−) mice. Differences in gene expression levels and patterns are thus an important determinant of pathotype in C. jejuni strains in this mouse model.